Pengaruh Profitabilitas, Struktur Modal Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Studi Pada Sektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Amelia Amelia; Wasti Reviandani (Jurnal Mirai Management, 2022)
The purpose of this study is to determine the effect of profitability, capital structure, and firm size on firm value. The population in this study is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling method was purposive sampling so that a total sample of 16 companies was obtained. The data analysis technique uses multiple linear regression analysis with SPSS version 29 program. The results in this study indicate that profitability has an effect on firm value, while capital structure and firm size have no effect on firm value. Keywords: Profitability, Capital Structure, Firm Size, Firm Value.